EPISTEMOLOGI TAFSIR ILMI KEMENAG: TUMBUHAN DALAM PERSPEKTIF AL-QURâAN DAN SAINS - Julkarnain, Muhammad (JURNAL PENELITIAN KEISLAMAN, 2014)
Differences about Tafsir Ilmi in study of Islamic scripture have lingered academic dispute in Islamic scholarship. Mostly the debates arouse in the relation of Quran and the development of science due to dynamic and actuality of science itself. It so does if we look at Tafsir ilmi of ministry of religious affairs in epistemological perspective, eventually there are some debates about meaning and significance of a word or a sentence. Therefore, this research is conducted in order to discover and explore the answer of such problems. This research applies descriptive and qualitative approach and library research, while in analyzing the data content analysis is preferred. The result of this research is Tafsir Ilmi: Plants in Quran and Science Perspective from ministry of religious affairs is a comprehensive effort to interpret phenomena of universe within which the plant is bound to. Rich and complex description and explanation ranging from theology to ethics are able to pose answer for the dispute in Tafsir Ilmi. Eventually an effort to discuss it in academic realm, the places wherein sciences and religions meet each other, should be done in order to reach comprehensive understanding of it.